322 Comparative Analysis of Endovascular Intervention and Endarterectomy in Patients with Femoral Artery Disease: A Systematic Review. (19th August 2022) - Sreejith, G; Ravikumar, N; Law, SHC; Anand, P; Varghese, N; Kagdi, S; Kang, N; Salam, S; Ongidi, I; Nashnoush, M
Abstract: Aim: To compare the safety and efficacy of endovascular stenting to endarterectomy in treating femoral artery disease. Method: We searched databases such as PubMed, Ovid, Embase and Scopus for studies done on endovascular and endarterectomy treatments in the last decade. The inclusion criteria comprised of latest studies within the last 10 years, human studies and restricting to only femoral artery disease. Relevancy of the articles were assessed using PRISMA and the Newcastle-Ottawa quality assessment scale. Thereafter, the data were extracted, and the statistical variables were calculated using MedCalc software. The PRISMA checklist was used to assess risk of bias. Results: Total of twenty-six retrospective, prospective and sub-analysis studies met the inclusion criteria with a total of 7126 patients (endovascular, 2496; endarterectomy, 4630). A division of the outcomes into primary and secondary were assessed based on direct correlation to the parameters evaluated. Our review demonstrated a higher value of technical success for endovascular intervention than endarterectomy with an odds ratio of 4.27 and statistically significant at 95% CI (2.87–6.38). In terms of safety, wound complications, and mortality (short and long-term) were evaluated. For wound infection, endovascular had better odds ratio of 0.65; 95% CI [0.51 to 0.81] and thus preferrable. Delayed wound healing and dehiscence occurred only in 0.15% of endovascular procedures in contrast to 0.99% in endarterectomy. There was no significant difference in both the mortality rates in the two groups appraised. Conclusions: Endovascular treatment of femoral artery disease is a safe and effective alternative to endarterectomy. It has a lower incidence of wound related and other perioperative complications.